2022
DOI: 10.4103/abr.abr_163_21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination Therapy with Bunium persicum and Foeniculum vulgare Extracts on Patients with Polycystic Ovary Syndrome

Abstract: Background: Considering the side effects of common drugs used to treat polycystic ovary syndrome (PCOS), researchers have turned their attention to natural compounds, including medicinal plants. Foeniculum vulgare has estrogenic properties and has been traditionally used to treat gynecological disorders. Bunium persicum has medical aspects that have not yet been evaluated, so the aim of this study was to evaluate the effects of combination ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Based on the results of numerous articles, black caraway has antioxidant, hypoglycemic, weight-reducing, antihypertensive, and antidyslipidemic properties. Possible mechanisms include (1) the reduction of ghrelin (appetite-stimulating hormone); (2) the reduction of production of visceral fat and, thereby lowering pro-inflammatory cytokines produced in these tissues (by carvacrol) (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of numerous articles, black caraway has antioxidant, hypoglycemic, weight-reducing, antihypertensive, and antidyslipidemic properties. Possible mechanisms include (1) the reduction of ghrelin (appetite-stimulating hormone); (2) the reduction of production of visceral fat and, thereby lowering pro-inflammatory cytokines produced in these tissues (by carvacrol) (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the testosterone level increased after receiving treatment [38,39,41,47,48]. Tumors have the potential to overproduce androgens, resulting in increased testosterone levels.…”
Section: Testosteronementioning
confidence: 99%
“…Progesterone, the synthesis of which depends on the corpus luteum, regulates reproductive cycles and assists the uterus in implantation during conception [74]. Progesterone levels significantly increased after treatment in several studies [39][40][41]46], and significantly decreased in another study [50,51]. Phytoestrogens contain compounds that mimic or interact with estrogen in the body.…”
Section: Progesteronementioning
confidence: 99%
See 1 more Smart Citation
“…Fennel has undergone extensive research revealing its numerous benefits, which encompass antimicrobial, antifungal, anti-inflammatory, antioxidant, anxiolytic, cardioprotective, and potential hormonal properties [13]. Notably, fennel acetone extract shows promise in menstrual cycle regulation [14], and it may affect hormone levels by increasing the follicle-stimulating hormone while decreasing the luteinizing hormone and testosterone [15]. Moreover, fennel essential oils notably influence oocyte maturation and sexual maturity in fishes [16,17].…”
Section: Introductionmentioning
confidence: 99%